EDUCAÇÃO FINANCEIRA PARA CRIANÇAS: NARRATIVAS INFANTIS - Bevilaqua Costa, Fernanda; Maria de Oliveira, Sônia; Aparecida de Sales Gonçalves, Marcela; Maia Marciano Matos, Marina (LINKSCIENCEPLACE, 2026)
This study aims to contribute to the process of financial education of the children of the 2nd / 3rd year of primary education, from E.E.M.V, city of Carangola / MG. He dealt mainly with the authors D’Aquino (2008), Faveri, Kroetz & Valentim (2012), Kiyosaki (2014) and Larossa (1998). Research has been carried out through an action research, developed a priori through two thematic workshops: 1) collection of children’s narratives about the concepts: money, expenses, donations and family savings; 2) Making the Dream Chart. Children’s narratives reveal an understanding of money, predominantly related to the pillars of winning and spending. Few children say that it is a common practice to save and give in the daily lives of families. Dreams reveal the marks of the desire to obtain material objects and obtain what money is not able to buy: love.